Lessons from the Virtual Delivery of Building Information Modelling Modules in the COVID-19 Era - Fonbeyin Henry Abanda; Avar Almukhtar; Mark Austin (Buildings)
Emerging building information modelling (BIM) can be complex to teach during a regular face-to-face class schedule, and even more challenging remotely or virtually. This has been further exacerbated by the outbreak of COVID-19 whereby the adoption of virtual teaching techniques in higher education has been strongly recommended. However, since the outbreak, in December 2019, there has been a paucity of research with regards to experiences with the virtual delivery of BIM. This study explores lessons learnt in engaging students through the virtual delivery of BIM courses during the COVID-19 pandemic. Quantitative data from a questionnaire and quantitative and qualitative data from the various module evaluation reports were used to inform this study. A main finding is that, despite being a technical course, BIM can still be delivered online without compromising any of its learning outcomes. In contrast to existing literature, the main contribution of this study is practical as it provides insights on methods that worked and those that can be used post-COVID-19 in delivering BIM courses. This study provides hope to prospective students, especially distance learning students, who often worry whether the technology aspects of BIM can be taught remotely. Although the study is grounded on BIM and driven by the COVID-19 context and distance learning, it has wider implications for learning and teaching in other technical disciplines and virtual learning in general. Specifically, the experiences and impacts of delivering BIM examined in this study can inform curricula design in other disciplines.